Problems to Be Solved by Inflation and How They Are Solved in Inflationary Models - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will present problems with the standard cosmology, before the advent of the inflationary paradigm, and then we will see how they are solved by inflation.